2012
DOI: 10.1073/pnas.1207866109
|View full text |Cite
|
Sign up to set email alerts
|

Na + /K + -ATPase E960 and phospholemman F28 are critical for their functional interaction

Abstract: Na + -K + -ATPase (NKA) establishes the transmembrane [Na + ] gradient in cells. In heart, phospholemman (PLM) inhibits NKA activity by reducing its apparent Na + affinity, an effect that is relieved by PLM phosphorylation. The NKA crystal structure suggests regions of PLM-NKA interaction, but the sites important for functional effects in live cells are not known. We tested wild type (WT) and CFP-NKA-α1 point mutants (alanine substitution at F956, E960, L964, and F967) for fluorescence resonance energy transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The latter may be only one of many physiological conformations but mutational analysis showed that the E960 residue on NKA TM9 and the F28 residue on PLM are critical for both the functional effects on the pump and NKA–PLM FRET (Khafaga et al . ). The co‐immunoprecipitation was not completely abolished by these mutations indicating that additional PLM–NKA interaction sites contribute to the robust physical association of PLM with NKA.…”
Section: The Na+/ca2+ Exchanger – Structure Function and Regulationmentioning
confidence: 97%
“…The latter may be only one of many physiological conformations but mutational analysis showed that the E960 residue on NKA TM9 and the F28 residue on PLM are critical for both the functional effects on the pump and NKA–PLM FRET (Khafaga et al . ). The co‐immunoprecipitation was not completely abolished by these mutations indicating that additional PLM–NKA interaction sites contribute to the robust physical association of PLM with NKA.…”
Section: The Na+/ca2+ Exchanger – Structure Function and Regulationmentioning
confidence: 97%
“…Molecular dynamics simulations suggest an interaction between the PLM carboxyl terminus (R65, R66, and R70) and the pump N domain may be responsible for at least part of this functional inhibition (33). The structural imposition of a membrane-anchoring fatty acid on PLM C40 may influence the interaction between elements of the PLM carboxyl terminus and the pump intracellular domains, but it is more probable that PLM palmitoylation influences the pump within the membrane bilayer itself, which is also a site of physical contact between these proteins (34,35). Palmitoylation is well established as regulating protein partitioning to membrane microdomains (36).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structures identified a number of possible interaction sites between FXYD and NKA-α TM9. In a recent study we demonstrated that interaction between NKA-α-E960 and PLM-F28 sites is critical for the functional effects of PLM on NKA [104]. The conserved FXYD motif is located in the extracellular domain, just prior to the TM domain and seems to interact with both α- and β-subunits.…”
Section: [Na+]i Transport In and Out Of Cardiac Myocytesmentioning
confidence: 99%